2010
DOI: 10.1007/s00125-010-1989-0
|View full text |Cite
|
Sign up to set email alerts
|

Decreased insulin secretion and increased risk of type 2 diabetes associated with allelic variations of the WFS1 gene: the Data from Epidemiological Study on the Insulin Resistance Syndrome (DESIR) prospective study

Abstract: Aims/hypothesis We investigated associations of allelic variations in the WFS1 gene with insulin secretion and risk of type 2 diabetes in a general population prospective study. Methods We studied 5,110 unrelated French men and women who participated in the prospective Data from Epidemiological Study on the Insulin Resistance Syndrome (DESIR) study. Additional cross-sectional analyses were performed on 4,472 French individuals with type 2 diabetes and 3,065 controls. Three single nucleotide polymorphisms (SNPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
4
23
0
Order By: Relevance
“…Therefore, carriage of the susceptibility WFS1 variant is related to impaired glucoseinduced insulin response resulting from β-cell dysfunction. These results are in accordance with findings in other populations reporting the relationship between the carriage of various diseaseassociated variants of WFS1 and altered insulin secretion in response to glucose stimulation [10,[19][20][21] and lower pancreatic β-cell function [22]. SNP rs734312 is a missense mutation that is situated in the last exon (exon 8) of WFS1, and leads to an amino acid (aa) substitution of histidine to arginine in codon 611 (H611R).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, carriage of the susceptibility WFS1 variant is related to impaired glucoseinduced insulin response resulting from β-cell dysfunction. These results are in accordance with findings in other populations reporting the relationship between the carriage of various diseaseassociated variants of WFS1 and altered insulin secretion in response to glucose stimulation [10,[19][20][21] and lower pancreatic β-cell function [22]. SNP rs734312 is a missense mutation that is situated in the last exon (exon 8) of WFS1, and leads to an amino acid (aa) substitution of histidine to arginine in codon 611 (H611R).…”
Section: Discussionsupporting
confidence: 90%
“…First evidence for association between WFS1 and T2D was obtained in a small study involving an analysis of UK families with T2D [4]. The association between WFS1 and T2D was then repeatedly replicated by several large-scale studies in various Caucasian populations [5][6][7][8][9][10]. In WFS1, several single nucleotide polymorphisms (SNPs) showed significant associations with T2D, with SNP rs10010131 as the most strongly diseaseassociated marker (for a minor allele A, odds ratio (OR) = 0.89, 95% confidence interval (95% CI) = 0.86-0.92) [7].…”
Section: Introductionmentioning
confidence: 95%
“…The WFS1 variant has been prospectively associated with development of type 2 diabetes among individuals of European ancestry [43]. For remaining loci, differences in linkage disequilibrium of the genotyped SNP with the ‘causal’ variant(s) between American Indians and individuals of European ancestry, the population used in the discovery, may account for some of the negative findings.…”
Section: Discussionmentioning
confidence: 99%
“…WFS1 null mice and genetic association studies suggest a role for the WFS1 gene in insulin secretion [48,49,50]. In a previous study, another novel variant, c.2017T>C:p.Arg703Cys, in WFS1 was also found in a Norwegian MODY family; however, the authors suggested further evaluation of the role of WFS1 in MODY considering an inheritance pattern [12].…”
Section: Discussionmentioning
confidence: 99%